Obtaining a social licence for MPAs – influences on social acceptability. (January 2015) - Voyer, Michelle; Gladstone, William; Goodall, Heather
Abstract: The biological success of Marine Protected Areas (MPAs) depends to a large extent on their social acceptability, sometimes referred to as a social licence. Local resistance has slowed international progress towards a global network of MPAs. The causes of local resistance and limited social acceptability are poorly known, which constrains the development of new planning paradigms that could address these issues. Two case studies in New South Wales, Australia determined the factors that influenced community attitudes towards MPAs. The Port Stephens-Great Lakes Marine Park (PSGLMP) and Batemans Marine Park (BMP) underwent virtually identical and concurrent planning processes, however resistance to the BMP was more intense and sustained. Differences in the demographics, history, local media coverage and social impacts of each marine park contributed to these different community responses. The BMP demonstrated the 'perfect storm' of opposition triggers – a community struggling in the transition away from a primary production economy, a highly politicised media dominated by powerful elites with ideological objections to the park, and social impacts sufficiently profound to motivate local citizens to support an active campaign against the park. These impacts included loss of access, identity and increased competition for resources. This research points to the importance of developing a deeper understanding of the social, cultural and political landscape of the communities in which MPAs are proposed and a rethink of planning processes to better incorporate community objectives and knowledge.